The hierarchy of states reform and resistance in the international order - Clark, Ian 1949- (Cambridge studies in international relations, 1989)
The hierarchy of states presents Ian Clark's Reform and resistance in the international order, a well-established text on international relations first published in 1980, in a completely revised form. Combining a detailed examination of theory with a full account of historical developments, Dr Clark analyses the nature of international order - the hierarchical state system - and its potential for reform. The theory of international order is explored tracing two traditions of thought epitomised in the writings of Kant and Rousseau, whilst in a historical survey Dr Clark covers the main attempts to implement international order since 1815 and includes such aspects as concert diplomacy, alliance systems, international organisations as well as such informal understandings as nuclear deterrence, crisis management and spheres of influence. This revised edition contains two new chapters - one on international/world order issues and the other on 'macro' changes between 1815 and 1990. Dr Clark has updated his discussion on the course of superpower relations and most of the material on the post-1945 period is introduced in this edition for the first time